A Corpus-driven Analysis of Lexical Frames in Academic Writing - Ang, Leng Hong (Pusat Pengajian Ilmu Kemanusiaan, 2019)
In recent years, there is a growing interest in understanding how multi-word sequences, particularly the continuous ones, are structured and used in academic discourse. For instance, in analysing academic prose, Biber et al. (1999) revealed that most continuous multi-word sequences, i.e. lexical bundles are not complete structural units in their corpus of academic writing. These lexical bundles often end in a function word, such as an article or a preposition (e.g. as a result of, the context of the). The few structurally complete bundles are usually phrases that function as discourse markers (e.g. in the first place, for the first time). A notable finding by Biber et al. (1999) is closely related to the potentially useful but much neglected discontinuous multi-word sequences. They found that most lexical bundles in academic prose consist of prepositional or nominal elements that co-occur in highly productive frames, such as the + * + of the + *. The two empty slots represented by the asterisk key * can be filled by many words to make different lexical bundles (e.g., the number of the patterns, the nature of the business).